APPROACHES TO FORMALIZATION OF MOTION DYNAMICS OF ARTIFICIAL FORCE FIELD METERS - Chepizhenko, Valery; Volkogon, Viktoriya (Proceedings of National Aviation University (archive), 2016)
Purpose: The aim of our study is to analyze virtual measurers with different functioning principles. In our case they are: a mathematical pendulum without quality factor, with quality factor and meter of force field gradient. Methods: This article reviews two main approaches for gradient or artificial force field measuring: gradient method and mathematical pendulum. Results: The results of our experiment proved that usage of the mathematical pendulum with quality factor is more effective than without it. We classified potential field methods concerning field types. Present approaches possess a number of shortcomings. Discussion: The paper considers modern approaches of solving conflict situations in airspace (traffic conflict). We carried out analysis of virtual indicators formalization with different functioning principles (mathematical pendulum, meter of force field gradient).